Conformational control through co‐operative nonconventional C—H…N hydrogen bonds. Issue 8 (26th July 2021) - Bosch, Eric; Bowling, Nathan P.; Oburn, Shalisa M.
Abstract : Co‐operative nonconventional sp 2 ‐C—H…N hydrogen bonds control the conformation of a dipyridyl molecule to a rhombus shape. Abstract : We report the design, synthesis, and crystal structure of a conjugated aryleneethynyl molecule, 2‐(2‐{4, 5‐dimethoxy‐2‐[2‐(2, 3, 4‐trifluorophenyl)ethynyl]phenyl}ethynyl)‐6‐[2‐(pyridin‐2‐yl)ethynyl]pyridine, C30 H17 F3 N2 O2, that adopts a planar rhombus conformation in the solid state. The molecule crystallizes in the space group P, with Z = 2, and features two intramolecular sp 2 ‐C—H…N hydrogen bonds that co‐operatively hold the arylethynyl molecule in a rhombus conformation. The H atoms are activated towards hydrogen bonding since they are situated on a trifluorophenyl ring and the H…N distances are 2.470 (16) and 2.646 (16) Å, with C—H…N angles of 161.7 (2) and 164.7 (2)°, respectively. Molecular electrostatic potential calculations support the formation of C—H…N hydrogen bonds to the trifluorophenyl moiety. Hirshfeld surface analysis identifies a self‐complementary C—H…O dimeric interaction between adjacent 1, 2‐dimethoxybenzene segments that is shown to be common in structures containing that moiety.